Penggunaan Media Berbasis Lingkungan Dalam Meningkatkan Kreativitas Anak Usia Dini - Komalasari, Dedeh; Septiani, Rika (Buletin Ilmiah Pendidikan, 2023)
This study was motivated by the lack of variety in early childhood education learning activities and a lack of inclination toward ideas, creativity, or toughness. The purpose of this study is to examine the effect of using environment – based learning media on students’ creativity in early childhood. The problem was devised about how the use of environment-based learning media increases the creativity of early childhood education. This study used a quantitative research design. The result of this study indicated the improvement of early childhood creativity by using environment-based learning media. The result showed that the t-test is 3.294 and the t-table is 1.796. This differentiable learning was used by providing game variation, stimulating the children to develop and try to choose activities accordance with their study style, and also getting the real experience of using the learning media from the surrounding environment. So that the children’s exploration and their imagination have the opportunity to develop creativity and critical thinking.